Bif‐1/Endophilin B1/SH3GLB1 regulates bone homeostasis. Issue 11 (26th June 2019) - Touyama, Kenya; Khan, Masud; Aoki, Kazuhiro; Matsuda, Miho; Hiura, Fumitaka; Takakura, Nana; Matsubara, Takuma; Harada, Yui; Hirohashi, Yuna; Tamura, Yukihiko; Gao, Jing; Mori, Kayo; et al.
Abstract: Skeletal tissue homeostasis is maintained via the balance of osteoclastic bone resorption and osteoblastic bone formation. Autophagy and apoptosis are essential for the maintenance of homeostasis and normal development in cells and tissues. We found that Bax‐interacting factor 1 (Bif‐1/Endophillin B1/SH3GLB1), involving in autophagy and apoptosis, was upregulated during osteoclastogenesis. Furthermore, mature osteoclasts expressed Bif‐1 in the cytosol, particularly the perinuclear regions and podosome, suggesting that Bif‐1 regulates osteoclastic bone resorption. Bif‐1‐deficient (Bif‐1 −/− ) mice showed increased trabecular bone volume and trabecular number. Histological analyses indicated that the osteoclast numbers increased in Bif‐1 −/− mice. Consistent with the in vivo results, osteoclastogenesis induced by receptor activator of nuclear factor‐κB (NF‐κB) ligand (RANKL) was accelerated in Bif‐1 −/− mice without affecting RANKL‐induced activation of RANK downstream signals, such as NF‐κB and mitogen‐activated protein kinases (MAPKs), CD115/RANK expression in osteoclast precursors, osteoclastic bone‐resorbing activity and the survival rate. Unexpectedly, both the bone formation rate and osteoblast surface substantially increased in Bif‐1 −/− mice. Treatment with β‐glycerophosphate (β‐GP) and ascorbic acid (A.A) enhanced osteoblastic differentiation and mineralization in Bif‐1 −/− mice. Finally, bone marrow cells from Bif‐1 −/− mice showed a significantly higher colony‐forming efficacy by the treatment with or without β‐GP and A.A than cells from wild‐type (WT) mice, suggesting that cells from Bif‐1 −/− mice had higher clonogenicity and self‐renewal activity than those from WT mice. In summary, Bif‐1 might regulate bone homeostasis by controlling the differentiation and function of both osteoclasts and osteoblasts (235 words). Abstract : Graphic summary of phenotype of Bif‐1 −/− mice.